Circular Dichroism Enhancement: Symmetric Meta‐Absorber‐Induced Superchirality (Advanced Optical Materials 21/2019). Issue 21 (4th November 2019) - Rui, Guanghao; Hu, Haifeng; Singer, Matthew; Jen, Yi‐Jun; Zhan, Qiwen; Gan, Qiaoqiang
Abstract : Strongly localized chiral optical fields can enhance the chiral light–matter interaction. In article number 1901038, Qiaoqiang Gan, Qiwen Zhan and co‐workers present a design for the generation of superchiral optical field using symmetric metamaterial superabsorber structures and demonstrate its application in enhanced circular dichroism (CD) spectroscopy. Simulations reveal that the optical chirality density and the CD signal can be enhanced by 80‐ and 1300‐fold, respectively, revealing a strategy to develop scalable platforms for chiroptical applications.